Performance evaluation of future AMI applications in Smart Grid Neighborhood Area Networks (2015)
Smart Grid constitutes the next generation of electricity delivery systems that intend to enhance reliability, efficiency, and security of the power grid. A fundamental component of this intelligent network is the Advanced Metering Infrastructure (AMI), which provides a two-way communication network between Utilities and a collection of smart meters located at the customers side. The interconnected meters form Neighborhood Area Networks that provide a platform for the deployment of customized AMI applications. In this paper, we study the operation of AMI in Colombia. While several Utilities are implementing first approximations to AMI that mostly focus on automated consumption readings, there is no certainty that traffic of different natures, corresponding to future AMI applications, can be supported by these initial deployments. As there is a lack of study of these issues, we carry out an extensive performance evaluation through simulations of current technologies delivering traffic from future AMI applications. Our simulations are based on an extensive review of the communication technologies that are currently employed for AMI in Colombia, and on a characterization of the future AMI applications. With our study we pursuit a better understanding of the primary challenges that will have to be faced for the development and enhancement of AMI networks in the country.